Alternative food chains as a way to embed mountain agriculture in the urban market: the case of Trentino - Emanuele Blasi; Clara Cicatiello; Barbara Pancino; Silvio Franco (Agricultural and Food Economics, 2015)
Peri-urban agriculture is exposed to multiple pressures, which push to diversification and multifunctionality. However, the urban-rural link develops in different ways according to the features of the territories. A very interesting case is that of mountain areas, where the proportion among urban and rural domain is very skewed towards the latter and, at the same time, farms face major environmental problems that in most cases jeopardize their competitiveness in the mainstream market. Alternative food chains may play a key role in these contexts, especially for their ability to put farms in touch with the demand of consumers living in the urban areas located in the valley. In this paper we study the case of Trentino, an Italian Alpine region where alternative food chains are quickly developing, by comparing the development of alternative markets in this context with other Italian peri-urban areas. The mountain environment makes it very difficult for farms to standardize their products according to the requirement of the large retailers. Through alternative food chains, the typicality of products and the savoir faire of the farmers - representing the two main factors of products' added value - are endorsed and more easily communicated to the market. Data from a survey conducted on short food chain consumers show that they are inherently more careful to these particular cues of the products, as a result of a lifestyle that makes them more attached to identity and origins, as well as being more proud of their territory. These evidences confirm that in the Trentino area, for its structural and cultural traits, alternative food markets are meaningful for the survival and development of the local agricultural sector.
Keywords: 330; Alterative food networks; Short food supply chains; Peri-urban agriculture; Rural-urban link; Mountain farming; Local products